PENGEMBANGAN MEDIA PEMBELAJARAN CERITA BERGAMBAR DIGITAL UNTUK MENINGKATKAN HASIL BELAJAR IPAS KELAS V MI DATUK SINGARAJA KERSO - Barokah Isdaryanti; Muhammad Roghib Rojiddin (Information Technology Education Department, 2026)
Science and social studies (IPAS) learning plays an important role in developing students’ scientific and social literacy from an early age. However, in Grade V at MI Datuk Singaraja Kerso, the learning process remains relatively monotonous, with repetitive media use and limited teacher competence in utilizing visual media, resulting in suboptimal delivery of abstract material. Based on this condition, this study aimed to develop digital picture story learning media to improve Grade V students’ IPAS learning outcomes. The study focused on developing and testing the feasibility and effectiveness of the media. This research employed a Research and Development (R&D) model using the ADDIE approach, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. Data were collected through observation, interviews, questionnaires, and document studies. Expert validation showed an average score of 91.3%, categorized as feasible. Teacher and student responses in both small- and large-scale trials also indicated very high acceptance, with scores ranging from 91.67% to 96.44%. The effectiveness of the media was evidenced by improvements in learning mastery, mean difference tests (0.001 for small-scale; 0.000 for large-scale), and N-Gain values (71.37% for small-scale and 65.98% for large-scale), with normally distributed data. These findings demonstrate that digital picture story learning media is both feasible and effective, enhancing student engagement and learning outcomes. The media also provides practical guidance for teachers in designing interactive and contextual digital learning experiences. Keywords: Picture Story; Digital; IPAS Learning; Learning Outcomes; Elementary Level.